2003
DOI: 10.1038/sj.bjc.6601242
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cumulative prognostic scores based on the systemic inflammatory response in patients with inoperable non-small-cell lung cancer

Abstract: A score based on the combination of the systemic inflammatory response and albumin hazards ratio (HR) 1.70, 95% CI 1.23 -2.35, P ¼ 0.001) was comparable in prognostic value to that based on stage and performance status (HR 1.48, 95% CI 1.12 -1.95, P ¼ 0.006) in patients with inoperable non-small-cell lung cancer. The former is simple to measure and well standardised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
642
3
15

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 682 publications
(676 citation statements)
references
References 17 publications
16
642
3
15
Order By: Relevance
“…This work is consistent with previous work in patients with inoperable nonsmall-cell lung cancer (Forrest et al, 2003(Forrest et al, , 2004(Forrest et al, , 2005 and improves on the prediction of survival using an elevated C-reactive protein alone (Albuquerque et al, 1995;Zhang and Adachi, 1999). If these results are confirmed in larger studies, the GPS may be useful in the assessment of advanced breast cancer patients at diagnosis and the stratification of patients entering randomised trials.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This work is consistent with previous work in patients with inoperable nonsmall-cell lung cancer (Forrest et al, 2003(Forrest et al, , 2004(Forrest et al, , 2005 and improves on the prediction of survival using an elevated C-reactive protein alone (Albuquerque et al, 1995;Zhang and Adachi, 1999). If these results are confirmed in larger studies, the GPS may be useful in the assessment of advanced breast cancer patients at diagnosis and the stratification of patients entering randomised trials.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, we have shown that, using established cutoffs, a combination of an elevated C-reactive protein and hypoalbuminaemia, the Glasgow Prognostic score (GPS) has prognostic value, independent of stage and performance status, in patients with inoperable non-small-cell lung cancer (Forrest et al, 2003(Forrest et al, , 2004(Forrest et al, , 2005. However, there is no information on the prognostic value of this combination in patients with metastatic breast cancer.…”
mentioning
confidence: 99%
“…An APPR has been well documented among patients with cancer, including gastric and oesophageal malignancies, and an elevated serum CRP has been identified as an adverse prognostic indicator, independent of stage of disease, among these patients (Rashid et al, 1982;Falconer et al, 1995;Kodama et al, 1999;McMillan et al, 2001McMillan et al, , 2003Nozoe et al, 2001;Forrest et al, 2003). The present study has confirmed these findings.…”
Section: Discussionsupporting
confidence: 85%
“…The presence of an APPR has been associated with weight loss, the presence of hypermetabolism and anorexia, extent of disease, the development of recurrence in advanced cancer, and adverse prognosis (independent of stage of disease) (Rashid et al, 1982;Kodama et al, 1999;McMillan et al, 2001McMillan et al, , 2003Nozoe et al, 2001;Forrest et al, 2003). In patients with gastric cancer, the presence of systemic inflammation has been associated with a markedly reduced median survival (9 vs 53 weeks, Po0.001) (Rashid et al, 1982).…”
mentioning
confidence: 99%
“…Indeed, this relationship between nutritional decline, albumin concentrations and the systemic inflammatory response has recently been exploited to form a new prognostic score in patients with advanced non-small-cell lung cancer (Forrest et al, 2003).…”
Section: Discussionmentioning
confidence: 99%